Development and applications of chromosome-specific BAC-FISH probes in Pacific abalone (Haliotis discus hannai) - Zhang, Jianpeng; Wang, Yi; Huang, Zekun; Cai, Mingyi; You, Weiwei; Lu, Ying; Luo, Xuan; Ke, Caihuan (Frontiers in Marine Science, 2023)
Pacific abalone (Haliotis discus hannai) is an economically important marine shellfish for aquaculture and is distributed throughout eastern Asia. Although a lot of genetic breeding work has been carried out, chromosome identification in abalone is still a challenging task. Here, we developed a set of BACs to be chromosome-specific probes in Pacific abalone, and to study chromosome evolution in the related species. Through BAC paired-end sequencing and sequence alignment, we were able to in silico anchor 168 BACs onto 18 pseudochromosomes of Pacific abalone genome. After selecting 42 BACs that contained DNA inserts with minimal repetitive sequences, we validated them through PCR and Fluorescence in situ hybridization (FISH) test. As a result, We obtained specific FISH signals for 26 clones on the chromosomes of Pacific abalone with at least one BAC mapped per chromosome. We also applied the chromosome-specific BAC-FISH probes to a close relative of Pacific abalone, Xishi abalone (H. gigantea), which revealed that chromosome 13 and 15 between the two species underwent a chromosomes rearrangement event. This study provides the first set of chromosome-specific probes for the family Haliotidae, which can serve as an important tool for future cytogenetics and genomics research.